2010
DOI: 10.1017/s095442241000020x
|View full text |Cite
|
Sign up to set email alerts
|

Ready-to-eat cereals and the burden of obesity in the context of their nutritional contribution: are all ready-to-eat cereals equally healthy? A systematic review

Abstract: A significant increase in the prevalence of obesity has occurred worldwide and the importance of considering the role of diet in the prevention and treatment of obesity is widely acknowledged. A growing body of evidence encourages the consumption of ready-to-eat cereals (RTEC) as part of a healthful diet. Research has shown an inverse association between the consumption of RTEC and the rate of obesity. However, other findings claim that this association was only attributed to the consumption of whole-grain cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 64 publications
3
17
0
Order By: Relevance
“…One of the explanations for the observed association of RTEC consumption with lower BMI is the association with lifestyle habits such as greater physical activity and reduced television watching ( 248 ). One prospective cohort study in the United States in 2379 girls compared the cumulative percentage of days that each girl consumed breakfast cereal in childhood with results from 30-d physical activity diaries.…”
Section: Resultsmentioning
confidence: 99%
“…One of the explanations for the observed association of RTEC consumption with lower BMI is the association with lifestyle habits such as greater physical activity and reduced television watching ( 248 ). One prospective cohort study in the United States in 2379 girls compared the cumulative percentage of days that each girl consumed breakfast cereal in childhood with results from 30-d physical activity diaries.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from these studies suggests that consuming RTEC for breakfast may play a role in overweight/obesity prevention. A systematic review conducted by Kosti et al (2010) included eight cross‐sectional, one longitudinal, and two RCTs supporting an inverse association between cereal consumption and excess adiposity among children ; one of the RCTs found that daily consumption of 33 ± 7 g RTEC, including pre‐sweetened varieties, resulted in reduced BMI relative to a control group receiving no intervention only when combined with nutrition education . A more recent systematic review and meta‐analysis published by de la Hunty et al (2013) found that regular consumption of breakfast cereals was associated with reduced BMI and risk of overweight among children and adolescents in 14 studies .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Several recent publications have also described a positive association between overall nutrient intakes and RTEC consumption in children and adults when compared with SK or OB eating patterns. [4][5][6][7][8] The 2010 Dietary Guidelines for Americans (DGA 2010) 9 recommends people "eat a nutrient-dense breakfast."…”
Section: Introductionmentioning
confidence: 97%